Pemanfaatan Pengaya Autocrat untuk Distribusi Hasil Asesmen Sumatif Secara Daring - Rohimat, Sonny (PASCASARJANA IAIN SYAIKH ABDURRAHMAN SIDDIK BANGKA BELITUNG, 2023)
Abstract Online learning assessments in various educational units make extensive use of Google Forms. However, the automatic issuance of grades accompanied by scores for each answer in multiple choice questions can result in answer key leaks. The purpose of this study is to describe the use of the Autocrat add-on to distribute summative assessment results online without displaying the value for each number. The research was conducted in a descriptive qualitative manner in five stages of activity, namely compiling summative assessment questions, making assessment evidence, installing Autocrat add-ons, testing and revision, and carrying out summative assessments. Based on the results of this study it is known that the Autocrat add-on can be used to distribute summative assessment results online. The use of this Autocrat add-on is combined with Google Forms, Google Spreadsheets, Google Slides, Email, and even with Canva. Asesmen pembelajaran daring di berbagai satuan pendidikan banyak memanfaatkan Google Forms. Akan tetapi, penerbitan nilai secara otomatis yang disertai nilai untuk tiap jawaban pada soal pilihan ganda bisa mengakibatkan kebocoran kunci jawaban. Tujuan penelitian ini adalah mendeskripsikan pemanfaatan pengaya Autocrat untuk mendistribusikan hasil asesmen sumatif secara daring tanpa menampilkan nilai untuk masing-masing nomor. Penelitian dilakukan secara kualitatif deskriptif dalam lima tahap kegiatan, yaitu penyusunan soal asesmen sumatif, pembuatan tanda bukti asesmen, pemasangan pengaya Autocrat, uji coba dan revisi, serta pelaksanaan asesmen sumatif. Berdasarkan hasil penelitian ini diketahui bahwa pengaya Autocrat dapat digunakan untuk mendistribusikan hasil asesmen sumatif secara daring. Pemanfaatan pengaya Autocrat ini dilkombinasikan dengan Google Forms, Google Spreadsheets, Google Slides, Email, bahkan dengan Canva.